Representasi Fungsi Dan Makna Ujaran Permintaan Dalam Surat Taha : Kajian Balaghah - Hidayat, Ridho; Rohanda, Rohanda; Alandira, Palendika; Taufiq, Wildan (Center of Language and Cultural Studies, 2024)
This research aims to explore the functions and meanings of kalam insya’ thalabi found in the verses of Surah Taha. The focus of the discussion is on identifying the functions, types, and meanings of insya’ thalabi, such as commands (amr), prohibitions (nahi), and questions (istifham). This study employs a qualitative research approach, utilizing a qualitative descriptive analysis method with a linguistic analysis framework. The primary source of data consists of verses from Surah Taha in the Qur'an containing insya’ thalabi. Data collection techniques include library research and textual analysis of Qur'anic verses. The data is analyzed through a balaghah lens to uncover the functions and meanings inherent in each form of kalam insya’ thalabi within Surah Taha.